Resistance response of drought and heat tolerant spring wheat lines against the cereal cyst nematode, heterodera filipjevi - Atiya, Osameh; Dababat, Abdelfattah A.; Erginbas-Orakci, Gul; Singh, Sukhwinder; Toktay, Halil (Ankara University Faculty of Agriculture, 2022)
Spot blotch caused by Bipolaris sorokiniana is a destructive disease of wheat worldwide. This study investigated the aggressiveness of B. sorokiniana isolates from different wheat-growing areas of Bolu province in Turkey on the cultivar Seri-82. Host susceptibility of 55 wheat cultivars was evaluated against the most aggressive isolate. Our results indicated that the cultivars Anafarta and Koç-2015 were the most resistant. A specific and sensitive qPCR assay was developed for detecting the pathogen in plant tissues and evaluating wheat plants with different resistance levels. Three primer sets, BsGAPDHF/BsGAPDHR, BsITSF/BsITSR, and BsSSUF/BsSSUR, were designed based on glyceraldehyde-3-phosphate dehydrogenase, internal transcribed spacers, and 18S rRNA loci of B. sorokiniana with detection limits of 1, 0.1, and 0.1 pg of pathogen DNA, respectively. The qPCR assay was highly sensitive and did not amplify DNA from the other closely related fungal species and host plants. The protocol differentiated wheat plants with varying degrees of resistance. The assay developed a useful tool for the quantification of the pathogen in the early stages of infection and may provide a significant contribution to a more efficient selection of wheat genotypes in breeding studies. In the present study, expression levels of PR proteins, phenylalanine ammonia-lyase, catalase, ascorbate peroxidase, and superoxide dismutase enzymes were upregulated in Anafarta (resistant) and Nenehatun (susceptible) cultivars at different post-infection time points, but more induced in the susceptible cultivar. The results showed considerable variation in the expression levels and timing of defense genes in both cultivars.